Reading the parables - Lischer, Richard (Interpretation: resources for the use of scripture in the church, 2014)
"Parables make up one-third of Jesus' speech in the New Testament. In this volume, Richard Lischer provides an expert guide to these parables and proposes an important distinction between reading and interpreting the parables.Emphasizing the importance of reading the parables versus interpreting them, Lischer asserts that reading offers a kind of breathing space to explore historical, literary, theological, and socio-political dimensions of the parables and their various meanings, whereas interpreting implies an expert and critical position that must be defended. In this volume, Lischer lays out four theories for reading parables: 1) parables obscure truth; 2) parables teach many truths; 3) parables teach one truth; and 4) parables undermine the truth. Ultimately, he concludes that biblical parables undermine dominant myths called "the truth" to shine light on the Truth that is Jesus, God's presence with us"--